The broken spine - St. James, Dorothy (St. James, Dorothy. Beloved bookroom mysteries, 2021)
Rescuing hundreds of precious books from her newly digitized library, spunky librarian Trudell Becket is forced to prove her innocence when the politician behind the library's demolition is murdered.